2018
DOI: 10.1097/sla.0000000000002239
|View full text |Cite
|
Sign up to set email alerts
|

Cause-specific Mortality in a Population-based Cohort of 9799 Women Treated for Ductal Carcinoma In Situ

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
60
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 28 publications
(37 reference statements)
11
60
1
1
Order By: Relevance
“…These new data were also compared with data from other large studies performed in several countries, especially The Netherlands, the United Kingdom (UK), Canada, and the United States (US). 2,9,10,[12][13][14][15][16] The overall rate of mammographically detected DCIS in both surveys was identical: 87.5%, in accordance with other series. 17 Microcalcifications remain the major abnormality (87% vs. 82.5% previously).…”
Section: Discussionsupporting
confidence: 88%
“…These new data were also compared with data from other large studies performed in several countries, especially The Netherlands, the United Kingdom (UK), Canada, and the United States (US). 2,9,10,[12][13][14][15][16] The overall rate of mammographically detected DCIS in both surveys was identical: 87.5%, in accordance with other series. 17 Microcalcifications remain the major abnormality (87% vs. 82.5% previously).…”
Section: Discussionsupporting
confidence: 88%
“…Many population-based studies examining the various treatments in patients with DCIS have confirmed a reduction in local recurrences with local therapies (mastectomy vs lumpectomy and lumpectomy plus radiotherapy vs lumpectomy alone) 4,5,6,15 ; however, most have reported no significant difference in breast cancer mortality. 4,5,6,7,8,15,16 …”
Section: Discussionmentioning
confidence: 99%
“…Women aged less than 50 years old have been shown to present with more aggressive tumors [41], yet there was no significant difference in tumor characteristics by age group (Table 1). It is known that DCIS with invasive micro infiltrations clinically unrecognizable are common among young women [17]. Invasive infiltrations are considered an important risk factor of death after DCIS diagnosis [42].…”
Section: Mortalitymentioning
confidence: 99%
“…Competing causes of death and all-cause mortality would allow to overcome these limitations. Few studies have compared all-cause mortality rates of women with DCIS to the general population, most of which are in northern Europe [14][15][16][17] and the US [18]. Considering the possible differences in prevention plans, detection and treatment approaches between countries [19][20][21][22], it becomes relevant to provide evidence on all-cause mortality for patients diagnosed with a DCIS in regions where is not yet available, such as Southern Europe.…”
Section: Introductionmentioning
confidence: 99%